SAE Technical Paper Series 1996
DOI: 10.4271/960366
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transfer Port Geometry on Scavenge Flow Velocities at High Engine Speed

Abstract: ABSTRACT2-D LDV measurements were performed on two different cylinder designs in a fired two-stroke engine running with wide-open throttle at 9000 rpm. The cylinders examined were one with open transfer channels and one with cup handle transfer channels.Optical access to the cylinder was achieved by removing the silencer and thereby gain optical access through the exhaust port. No addition of seeding was made, since the fuel droplets were not entirely vaporized as they entered the cylinder and thus served as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In a former study on the two cylinder types, laser doppler velocimetry (LDV) was used to study the incylinder flow during gas exchange [17]. The same system has also been used to measure the flow outside the exhaust port.…”
Section: Velocity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a former study on the two cylinder types, laser doppler velocimetry (LDV) was used to study the incylinder flow during gas exchange [17]. The same system has also been used to measure the flow outside the exhaust port.…”
Section: Velocity Measurementsmentioning
confidence: 99%
“…The system used was a DANTEC fiber-flow with BSA signal processors. More information on the system can be found in [17].…”
Section: Velocity Measurementsmentioning
confidence: 99%
“…Laser Doppler Velocimetry measurements allowed, as reported for example in [7,8], to characterize the velocity field at the exit of intake ports of a Two-Stroke engine. This helped assessing the goodness of different intake geometries in improving SE.…”
Section: Introductionmentioning
confidence: 99%
“…To date, asymmetrical in-cylinder flow has been reported for a very limited range of two-stroke cycle engines. The studies that have reported asymmetrical flow fields and their adverse effects in loopscavenged two-stroke cycle engines, which were considered to be geometrically symmetrical about a nominal symmetry plane, have been published in references [1] to [7].…”
Section: Introductionmentioning
confidence: 99%
“…In 1996, Ekenberg and Johansson [7] investigated the effect of transfer duct geometry on scavenge flow velocities by making two-dimensional LDV measurements on two different cylinder designs in a fired two-stroke cycle engine at 9000 r/min. Optical access was achieved through the exhaust port.…”
Section: Introductionmentioning
confidence: 99%